Severe diaphragmatic dysfunction with preserved activity of accessory respiratory muscles in a critically ill child: a case report of failure of neurally adjusted ventilatory assist (NAVA) and successful support with pressure support ventilation (PSV) - Langer, Thomas (BMC Pediatr, 2019)
BACKGROUND: Neurally adjusted ventilatory assist (NAVA) is an alternative to pressure support ventilation (PSV) potentially improving patient-ventilator interaction. During NAVA, diaphragmatic electrical activity (EAdi) is used to trigger the ventilator and perform a proportional respiratory assistance. We present a case in which the presence of severe bilateral diaphragmatic dysfunction led to a failure of NAVA. On the contrary, the preserved activity of the accessory inspiratory muscles allowed a successful respiratory assistance using PSV. CASE PRESENTATION: A 10-year-old girl developed quadriplegia after neurological surgery. Initially, no spontaneous breathing activity was present and volume controlled ventilation was necessary. Two months later spontaneous inspiratory efforts were observed and a maximal negative inspiratory force of − 20 cmH(2)O was recorded. In addition, a NAVA nasogastric tube was placed. The recorded EAdi signal, despite showing a phasic activity, had a very low amplitude (1–2 μV). Two brief (15 min) breathing trials to compare PSV (pressure support = 8 cmH(2)O) with NAVA (Gain = 5 cmH(2)O/μV, inspiratory trigger = 0.3 μV) were performed. On PSV, the patient was well adapted with stable tidal volumes, respiratory rates, minute ventilation, end-tidal and venous carbon dioxide levels. When switched to NAVA, her breathing pattern became irregular and she showed clear sign of increased work of breathing and distress: tidal volume dropped and respiratory rate rose, leading to an increase in total minute ventilation. Nevertheless, end-tidal and venous carbon dioxide rapidly increased (from 49 to 55 mmHg and from 52 to 57 mmHg, respectively). An electromyographic study documented an impairment of the diaphragm with preserved activity of the accessory inspiratory muscles. CONCLUSIONS: We document the failure of mechanical assistance performed with NAVA due to bilateral diaphragmatic dysfunction in a critically ill child. The preserved activity of some accessory respiratory muscles allowed to support the patient effectively with pressure support ventilation, i.e. by applying a pneumatic trigger. The present case underlines (i) the importance of the integrity of the respiratory centers, phrenic nerves and diaphragm in order to perform NAVA and (ii) the possible diagnostic role of EAdi monitoring in complex cases of weaning failure.